Body Image, Eating Disorders, and Obesity in Youth: Assessment, Prevention, and Treatment. (2nd Ed).
DOI: 10.1037/11860-003
|View full text |Cite
|
Sign up to set email alerts
|

Body image in girls.

Abstract: Positive body image plays a vital role in fostering healthy psychological and physical development in girls. Conversely, poor body image has a wide range of negative consequences. In this chapter we provide a general back ground about the nature of body image in girls and the consequences of poor body image. We describe epidemiological research and risk factors related to body image and body disturbance in girls. Models for the development of body image disturbance are also described. Finally, prospective rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
4

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 73 publications
3
38
1
4
Order By: Relevance
“…This could be considered an unexpected finding given the gender differences on BID reported in previous studies, with girls reporting higher levels of BID than boys [33,37]. Nevertheless, it should be emphasized that the absence of a moderating effect of gender is not the same as the absence of gender differences.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This could be considered an unexpected finding given the gender differences on BID reported in previous studies, with girls reporting higher levels of BID than boys [33,37]. Nevertheless, it should be emphasized that the absence of a moderating effect of gender is not the same as the absence of gender differences.…”
Section: Discussioncontrasting
confidence: 39%
“…During adolescence, there are several unique biological and psychosocial challenges (e.g., puberty-related changes, school transitions) that may negatively influence individual psychosocial adjustment [1,20] and contribute to a heightened dissatisfaction with appearance [34,36]. Gender differences have also been found, with girls reporting higher levels of BID than boys [33,37]. In general, girls are more likely to worry about thinness, whereas boys tend to be concerned with their weight and muscularity [33,38,39].…”
Section: Introductionmentioning
confidence: 96%
“…The finding adds further support to the suggestion that by age 6 girls have already begun to internalize contemporary sociocultural beauty ideals. This is particularly concerning given the demonstrated links between body dissatisfaction and other negative psychological health outcomes such as disordered eating (Stice, 2002) and reduced self-esteem (Wertheim, Paxton, & Blaney, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For example, in their review of girls' body image, Wertheim, Paxton, and Blaney (2009) reported estimates of between 40 and 50 per cent for the number of pre-adolescent girls wishing to be thinner. Although most of the studies have sampled girls aged 9 years and above, some research indicates that weight concerns arise earlier, around 5 to 6 years of age (Davison, Markey, & Birch, 2000Dohnt & Tiggemann, 2005, 2006a.…”
Section: Contemporary Girlhood: Maternal Reports On Sexualized Behavimentioning
confidence: 99%
“…Although most of the studies have sampled girls aged 9 years and above, some research indicates that weight concerns arise earlier, around 5 to 6 years of age (Davison, Markey, & Birch, 2000Dohnt & Tiggemann, 2005, 2006a. Furthermore, as is the case with adult and adolescent women, pre-adolescent body dissatisfaction has been implicated as a precursor for subsequent dieting and disordered eating, as well as poorer psychological well-being (Smolak & Thompson, 2009;Wertheim et al, 2009).…”
Section: Contemporary Girlhood: Maternal Reports On Sexualized Behavimentioning
confidence: 99%